Evaluating the Srettha Thavisin Governmental Policy to Admit Migrant Workers: Model Process and Implementing Policies in Samut Sakhon Province - Charoensuk, Khotchatrai; Kesorn, Charin (Journal of Multidisciplinary Academic Research and Development (JMARD), 2025)
This research studied 1) policy implementation to admit migrant workers by the government of Srettha Thavisin in terms of contextual environment, primary input factors, process and results; 2) factors related to and 3) affecting the success of policy implementation for admitting migrant workers. Using a quantitative research model in the study according to the evaluation model concept according to the CIPP Model as a research framework. The sample group comprised 445 policy stakeholders chosen by convenience sampling. The data were analyzed using inferential statistics, including correlation analysis and multiple regression analysis. Results revealed 1) an overall high level ( = 3.61, S.D. = 0.440) of policy evaluation for admitting foreign workers by the Srettha government according to the CIPP model; 2) contextual factors, the environment, initial input factors, processes, and outcome were positively related to the success of implementing the policy to admit foreign workers at a statistical significance of .01; 3) initial input factors, processes, outcomes, and contextual environment impacted the success of policy implementation for admitting foreign workers, with beta values of Beta .551, .266, .244, and -.202, respectively, at a statistical significance of .05.